Documenting the Interactive Effects of Project Manager and Team-Level Communication Behaviors in Integrated Project Delivery Teams. Issue 1 (February 2022) - Manata, Brian; Miller, Vernon D.; Mollaoglu, Sinem; Garcia, Angelo J.
This study examines the influence of project managers' communication behaviors in integrated project delivery (IPD) projects. This study also considers the impact of team-level information sharing on team-level outcomes (i.e., goal alignment, decision quality, process commitment, and project quality). Results indicate that team information sharing was perceived as beneficial, but the effects of project manager communication behaviors were inconsistent. Interaction analyses indicated that project managers' communication behaviors hindered team functioning if teams were already engaging in adequate levels of information sharing. This manuscript contributes to the project management corpus by explicating an integrative model whereby project manager and team-level information-sharing behaviors are modeled simultaneously.